Gendering Heterodoxy: The Corporeal Politics of Xiejiao in Chinese Christianity - Yuan, Xiaobo (Journal of the American Academy of Religion, 2021)
In contemporary Christian communities in mainland China, heterodox religious organizations—most often referred to as xiejiao (“evil cults”)—have been seen as perennial threats to the proper functioning of the church. State and church authorities warn against the popularization of millenarian sects like Eastern Lightning/Church of Almighty God, and ordinary churchgoers are frequently exhorted to police each other (and themselves) against heterodox thoughts and actions. This paper explores the constitution of xiejiao as an intimate threat within Chinese Protestant communities. In particular, I attend to how rural women are represented as particularly “at risk” of propagating and receiving “heterodox” religious instruction. Drawing on ethnographic research and discursive analysis, I argue that the gendered and classed dimensions of anti-cult discourse suggest a broader corporeal politics of religious identity in which spiritual endangerment and responsibility are unevenly distributed among social bodies.